La participación de Mujeres de la Confederación del Pueblo Kayambi y su consolidación como representantes políticas en el movimiento indígena – 2019. - Reinoso Farinango, Betty Johana (2024)
The women of the Kayambi People's Confederation have marked a presence in various spaces as political representatives. However, there is little visibility within the indigenous movement, their participation has been devalued despite the fact that it plays a fundamental role in the organizational structure of the indigenous movement. This research work analyzes the different situations faced by indigenous women to recognize their actions. As an objective of the research, the dynamics of participation of the indigenous women of the Confederation of the Kayambi People will be diagnosed to consolidate themselves as political representatives in the indigenous movement 2019. Likewise, methodologically the research is based on a bibliographic exploration and to achieve a better understanding With the obtaining of information from the first source, interviews will be carried out with fellow presidents who are leaders of the organizations of the Kayambi People's Confederation and in this way demonstrate the leadership of Kayambi women in politics. Keywords: Social struggle, indigenous woman, indigenous movement, political representatives.